Are BUMN/State-Owned Enterprises (SOES) Hybrid Organizations? (Universitas Negeri Semarang, 2020)
The organization is now well developed. The organization does not only consist of public and private organizations, but also mixed organizations (hybrid organizations). And it’s influence to the organizations of State-Owned Enterprises (SOEs) as stated in the legal considerations of Constitutional Court (MK) Decision Nr. 48 and 62 / PUU-XI /2013 that exclaims that SOEs are private legal entities that carry out public duties. Referring to this matter, (a) elements of hybridity in SOEs, (b) benefits and risks in the form of hybrid SOE organizations, (c) the concept of hybridity in increasing the achievements of SOE objectives. By using an analytical approach and legislation results that based on the characteristics of BUMNs are categorized as hybrid organizations. As a hybrid organization has benefits and risks as a result of the influence of the public and private elements. The greatness of the benefits and risks of hybrid organizations is inversely proportional to the size comparison of public and private elements. The hybrid concept at Perum (Public Company) which aims for public benefit is a balanced public element with a private element. Whereas for Persero (State Company) that has commercial aims, the private element must be more dominant to create flexibility that drives the development of the Company. It is recommended that the concept of hybridity in SOEs must be adapted to the form of the company and the objectives of the company.